SISTEM INFORMASI VIA SMS GATEWAY ANTARA PIHAK KEPOLISIAN DENGAN PENGEMUDI - Ratna Adil (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Sum up accident sacrifice at January period of up to August 2007 progressively mount and primary factor of cause the happening of accident is human being factor, one of them is missing driver of awareness. To lessen this accident number, one of them is earn conducted by killing car machine in order to the missing driver of awareness cannot animate its car machine as well as communications with party police. The making of information system via SMS Gateway of between party police with driver, expected to by earn to overcome the problem. In this system, there are two sides that is side of driver and side police. Data of co-ordinate of position vehicle taken by GPS then is delivered through SMS of through server/police. That Data co-ordinate then is presented at digital map. Data of number Vehicle delivered through SMS to server and kept in database. With exploiting technology GPS (Global Positioning System), Microcontroller, GSM Modem, MapInfo, and Microsoft Office Access for the data intake, conducted a examination several times in place which equal to time difference about minute half, so that be got by a difference apart between position result of examination with data of reference of Google Earth of equal to more or less one meter. Others also be happened by the data deviation between position got from intake of data GPS with position vehicle which in fact (reference data from Google Earth). The based on result of examination which have been conducted in place location park D3 PENS ITS differ from position vehicle which in fact and happened by the position deviation more or less four transversal meter on course south (- 7,165614°) and the east longitude (112,476011°).